2021
DOI: 10.4103/idoj.idoj_226_20
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Alcohol Use Disorder and Chronic Plaque Psoriasis

Abstract: Background: Association between alcohol consumption, alcohol use disorder, and clinical features of psoriasis patients has not been adequately studied in the Indian context. Objectives: To study the frequency of alcohol consumption, alcohol use disorder, and its association with age, gender, duration, and severity of psoriasis. Materials and Methods: One hundred and forty-six (M: F 6.3:1) patients completed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
0
5
1
Order By: Relevance
“…While smoking or drinking habit did not directly impact patients' quality of life in our finding, studies found that heavy smokers (more than 20 cigarettes per day) significantly increased the risk of severe psoriasis [22]. In addition, a study shows that 32.9% of drinkers had a higher risk of developing severe psoriasis compared to 67.1% of non-drinkers [23]. Further analysis needs to be performed to study the role of smoking and drinking habits in psoriasis patients' QoL.…”
Section: Psoriasis and Qolcontrasting
confidence: 47%
“…While smoking or drinking habit did not directly impact patients' quality of life in our finding, studies found that heavy smokers (more than 20 cigarettes per day) significantly increased the risk of severe psoriasis [22]. In addition, a study shows that 32.9% of drinkers had a higher risk of developing severe psoriasis compared to 67.1% of non-drinkers [23]. Further analysis needs to be performed to study the role of smoking and drinking habits in psoriasis patients' QoL.…”
Section: Psoriasis and Qolcontrasting
confidence: 47%
“…These findings were confirmed by a study ofn 146 patients with psoriasis evaluating alcohol consumption using the Alcohol Use Disorder Identification Test (AUDIT) questionnaire [96]. In that study, regular drinkers (AUDIT score > 8) had more severe psoriasis than patients with an AUDIT score < 8 (p < 0.05) [96]. Furthermore, a study conducted on 95 patients with psoriasis, which investigated the link between alcohol consumption and psychological distress, also found a modest but significant association between psoriasis severity and weekly alcohol consumption (r = 0.27, p = 0.02) [97].…”
Section: Alcohol Abstinencementioning
confidence: 72%
“…As to the former aspect, a study on study on 29 patients with moderate plaque psoriasis found that alcohol consumption evaluated through questionnaires and an alcohol-specific blood biomarker (i.e., phosphatidylethanol) correlated significantly with the PASI score [95]. These findings were confirmed by a study ofn 146 patients with psoriasis evaluating alcohol consumption using the Alcohol Use Disorder Identification Test (AUDIT) questionnaire [96]. In that study, regular drinkers (AUDIT score > 8) had more severe psoriasis than patients with an AUDIT score < 8 (p < 0.05) [96].…”
Section: Alcohol Abstinencementioning
confidence: 85%
“…Another 67.1% of patients abstained entirely from alcohol consumption (AUDIT score 0). The remaining 13% regularly drank (AUDIT score ≥8) and had a more severe disease course compared to abstainers ( P <0.05) [ 54 ]. An important limitation of Mahajan et al’s study was that some individuals, especially women, might have feared the stigma associated with disclosing their alcohol use, and the study lacked follow-up with respondents after they had reduced their intake or given up alcohol [ 54 ].…”
Section: Discussionmentioning
confidence: 99%